HYGIENE SANITASI PENGOLAHAN DAN PEMERIKSAAN ESCHERICHIA COLI DALAM PENGOLAHAN MAKANAN DI INSTALASI GIZI RUMAH SAKIT UMUM PUSAT H. ADAM MALIK TAHUN 2012 - Netti Marpaung; Devi Nuraini Santi; Irnawati Marsaulina (Lingkungan dan Kesehatan Kerja, 2012)
Processing Sanitation Hygiene And Laboratory Analysis E.coli  in Nutrient Installation Of General Hospital H.Adam Malik. Food processing sanitation hygiene is intended to make better health life and to avoid disease. The application of the principle of food processing sanitation hygiene was carried out before food production, during manufacturing process, storage, transportation up to serving the food. The objective of this research was to know the description of sanitation hygiene and the contents of Escherichia coli in cooked food and the appliances of stainless steel plates in nutrient installation of general hospital H. Adam Malik. The method used was descriptive by observing the description of sanitation hygiene and laboratory analysis to the content of E.coli in cooked food product and stainless steel plate. The data was obtained with interview and observation. The result of research showed that nutrient installation of general hospital H. Adam Malik in sanitation hygiene fulfilled health requirements in accordance with Decision of Health Ministry RI No.1098/Menkes/SK/VII/2003 with total score 783,5 (>700) even though some points did not fulfill health requirements as in manufacturing food, cooked food storage and laboratory analysis, which  from 6 samples of cooked food checked in the laboratory and 2 samples did not fulfill health requirements since it contained E.coli. Stainless steel eating plate appliances were still in safe limit accordance with Decision of Health Ministry RI No.1098/Menkes/SK/VII/2003. Based on the result of research, it is necessary to supersive and give counseling regarding nutrient installation in hospital H. Adam Malik about the importance of food sanitation hygiene and appliances tools in food processing to fulfill health requirements. Key words : Sanitation, Escherichia coli, Food, Appliances